Análise das estruturas narrativas de jogos massive multiplayer online role playing game - Eduardo, João Pedro Osawa Vaz (2019)
This study has the objective of analysing the narrative’s structure of the games Ragnarok Online (RO), World of Warcraft (WoW), Star Wars: The Old Republic (SWTOR) e Elite: Dangerous (ED) in order to understand how these game’s stories were implemented and the relation of massive multiplayer game’s players with its narrative. The chosen games are categorized as Massive Multiplayer Online (MMO) games and they have some features of Role Playing Games (RPG). With a great presence of narrative elements, these games also allow the players to interact with each other in a world that evolves even when they’re not playing them. Thus, the analysis seeks to understand how this amount of people interacting at the same time was considered when determining these virtual environment’s narrative aspects. These games were chosen due to the amplitude of the virtual world in which the narrative is inserted. The players are presented to a story that helps compose the environment around them and, from that, they’re stimulated to explore the maps in seeking to develop the narratives created by the game developers or to create their own. Many similarities were observed among the narrative structures of the studied games, which present main stories linked to the users’ characters. In the game RO, the development of this narrative line doesn’t depend on the characters’ class, differently from the games WoW and SWTOR, that have a main story to each playable class. Furthermore, ED has proved to be and exception for it didn’t present a narrative line to the players’ characters.